2019
DOI: 10.3389/fpsyg.2019.02568
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Weiss-Harter-Model: Physical Activity, Self-Esteem, Enjoyment, and Social Support in Children and Adolescents

Abstract: Background: Several theories have been established to explain physical activity (PA) participation. However, many of these theories might not be applicable to adolescent PA behavior as they require a high level of cognitive reflection. Weiss suggests a model for youth which is based on the theoretical concept of Harter, focusing on self-esteem within social, emotional, and developmental aspects to explain behavior. The aim of this study was to test the original and a social support focused alternative version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 81 publications
3
18
2
Order By: Relevance
“…The initial model (Figure 1) was developed through the creation of four variables and a latent variable (physical self-concept) formed by physical appearance, physical condition, perceived competence, self-esteem, and perceived strength. This initial model showed the following fit indices, MRLχ 2 = 187.099, p < 0.05, CFI = 0.90, TLI = 0.87, SRMR = 0.09, and RMSA = 0.10, which were not acceptable; therefore, it was decided to restructure the model following the principles of previous research where such predictions are justified, such as the following: the predictive role of perceived competence in self-esteem [60]. In this sense, the model was restructured based on the proposals of the theoretical model presented by Fox and Corbin (1989) [56], establishing self-concept as a multidimensional variable formed by different domains, whose most important domain is self-esteem followed by perceived competence, fitness, perceived strength, and appearance.…”
Section: Structural Equation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial model (Figure 1) was developed through the creation of four variables and a latent variable (physical self-concept) formed by physical appearance, physical condition, perceived competence, self-esteem, and perceived strength. This initial model showed the following fit indices, MRLχ 2 = 187.099, p < 0.05, CFI = 0.90, TLI = 0.87, SRMR = 0.09, and RMSA = 0.10, which were not acceptable; therefore, it was decided to restructure the model following the principles of previous research where such predictions are justified, such as the following: the predictive role of perceived competence in self-esteem [60]. In this sense, the model was restructured based on the proposals of the theoretical model presented by Fox and Corbin (1989) [56], establishing self-concept as a multidimensional variable formed by different domains, whose most important domain is self-esteem followed by perceived competence, fitness, perceived strength, and appearance.…”
Section: Structural Equation Modelmentioning
confidence: 99%
“…In this sense, the model was restructured based on the proposals of the theoretical model presented by Fox and Corbin (1989) [56], establishing self-concept as a multidimensional variable formed by different domains, whose most important domain is self-esteem followed by perceived competence, fitness, perceived strength, and appearance. In this sense, perceived competence is the extent to which one judges oneself as capable in a certain area of life, which is why the higher the perceived competence, the greater the probability that they will present good self-esteem [60]. Consecutively, it was adjusted according to the effect of physical condition on quality of life in addition to its role in mental well-being [51].…”
Section: Structural Equation Modelmentioning
confidence: 99%
“…They also proposed the efficacy of individual and community level strategies that enhance the physical activity of the children should be included and evaluated. Similarly, Jekauc et al, (2019) investigated the impact of availability of physical equipment, finance, logistic, emotional support, and reinforcement by parents on children's sports participation. They found that there was an…”
Section: Parental Perception About Sportsmentioning
confidence: 99%
“…Longitudinal studies predominantly indicate that social cognitive factors such as self-efficacy and social support are central factors for the prediction of PA behavior change in general (Dishman et al, 2017;Jekauc et al, 2019;Kahn et al, 2002;Lewis et al, 2002;C. R. Nigg, 2001;Rhodes & Quinlan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…R. Nigg, 2001;Rhodes & Quinlan, 2015). Findings regarding enjoyment and knowledge about PA (knowing the benefits of PA) are inconsistent in terms of PA behavior change (Dishman et al, 2017;Jekauc et al, 2019;Kahn et al, 2002;Lewis et al, 2002;C. R. Nigg, 2001;Rhodes & Quinlan, 2015).…”
Section: Introductionmentioning
confidence: 99%